Attitude towards pre-marital genetic screening among students of osun state polytechnics, Nigeria (2012)
This study investigated the attitude towards pre-marital genetic screening among students of Osun State Polytechnics. Descriptive survey design was used for the study. The instrument for data collection was self developed and structured questionnaire in four- point likert scale format. Descriptive statistics of frequency count and percentages were used to describe the demographic data, while the parametric statistics oft-test and ANOVA set at 0.05 alpha level were used to test the hypotheses. A total number of one thousand, one hundred and sixty-five [1,165] Higher National Diploma [HND] students served as respondents for the study. Multistage sampling technique was used in three stages to select the respondents, namely: purposive sampling technique was used to select the schools; stratified sampling technique was used to select the Faculties and Departments, while proportionate sample of 25% was selected from each stratum. Three hypotheses were formulated to guide the study. The following were the values obtained: Difference in Attitude towards Pre-marital Genetic Screening [Crit-t = 1.96, Cal.t = 1.310, df = 1163, P > .05]; Difference in Attitude Due to Religion [F[2,1162] = .689, P > .05] and Difference in Attitude Due to Course of Study (F[5,1159] = .585, P > .05]. Conclusions were drawn based on the findings of the study. The study recommended, among other things that religious organizations should serve as useful channels to disseminate health information since people always have respect for places of worship and religious leaders.